Ultrasound Measurements of the First Extensor Compartment: Determining the Transection Limits for Ultra-minimally Invasive Release of De Quervain Tenosynovitis. (September 2021) - McCool, Logan; Tonkin, Brionn; Guo, Danqing; Guo, Danzhu; Senk, Alexander
Background: De Quervain syndrome is the second most common compressive tendinopathy. Although the length of the first extensor compartment (FEC) has been studied previously, there is no documented reported comparison study of short-axis and long-axis sonographic measurements. The thread technique, or Guo Technique, has been applied to carpal tunnel syndrome, trigger finger, and superficial peroneal compressive neuropathy. To perform this procedure, it is critically important to accurately identify the boundaries for transection.Methods: Twenty-one fresh frozen cadaver upper extremities were examined under ultrasound to determine the length of the extensor retinaculum (ER) over the FEC. Using the sonographic landmarks, the ERs were measured in short axis and long axis over their proximal to distal margins and from the distal margins to the distal edges of the radial styloids. These sonographic measurements were then compared with gross anatomical measurements.Results: The short-axis sonographic measurement of the ER on average was 22.53 mm (95% confidence interval [CI] = 20.79-24.05 mm). The long-axis sonographic measurement of the ER on average was 15.65 mm (95% CI = 13.70-17.78 mm). The average length of the ER by gross anatomical dissection was 22.40 mm (95% CI = 21.15-23.51 mm).Conclusions: The short axis is not significantly different from the gross anatomical measurement; however, the long axis is significantly lower than the gross anatomical measurement. The results support the idea that the short axis is more accurate than the long axis.